Phase transitions in a system of long rods on two-dimensional lattices by means of information theory - Vogel, E. E. (2017)
The orientational phase transitions that occur in the deposition of longitudinal polymers of length k (in terms of lattice units) are characterized by information theory techniques. We calculate the absolute value of an order parameter δ, which weights the relative orientations of the deposited rods, which varies between 0.0 (random orientation) and 1.0 (fully oriented in either of the two equivalent directions in an L×L square lattice). A Monte Carlo (MC) algorithm is implemented to induce a dynamics allowing for accommodation of the rods for any given density or coverage θ (ratio of the occupied sites over all the sites in the lattice). The files storing δ(t) (with time t measured in MC steps) are then treated by data recognizer wlzip based on data compressor techniques yielding the information content measured by a parameter η(θ). This allows us to recognize two maxima separated by a well-defined minimum for η(θ) provided k≥7. The first maximum is associated with an isotropic-nematic (I-N) phase transition occurring at intermediate density, while the second maximum is associated with some kind of nematic-isotropic transition at high coverage. In the cases of k<7, the curves for η(θ) are almost constant, presenting a very broad maximum which can hardly be associated with a phase transition. The study varies L and k, allowing for a basic scaling of the found critical densities towards the thermodynamic limit. These calculations confirm the tendency obtained by different methods in the case of the intermediate-density I-N phase transition, while this tendency is established here in the case of the high-density phase transition.